2010
DOI: 10.1097/ta.0b013e3181d27928
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Response to Reamed Intramedullary Nailing of the Femur Comparing Traditional Reaming With a One-Step Reamer-Irrigator-Aspirator Reaming System: An Experimental Study in Pigs

Abstract: The pattern of the procedure-related hemodynamic and pulmonary effects did not differ significantly between the RIA and the TR groups. The RIA group had lower numbers (ns) of embolisms per square centimeter lung area than the TR group. After reaming with the TR device, two animals died of PEs, the first postoperative day. The patients with femoral shaft fracture and additional cardiopulmonary injury or preexisting reduced cardiopulmonary function, however, need special attention, and the use of RIA may, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
15
0
2
Order By: Relevance
“…Other authors have examined venting the canal during intramedullary reaming but the significance in the oncologic population has yet to be elucidated [12][13][14]. Use of the RIA in animal models has demonstrated lower numbers of pulmonary emboli and lower intramedullary pressures when compared with traditional reaming [15,16]. In our small series, 6 patients had pulmonary metastases and compromised lung function, while 5 patients had brain metastases.…”
Section: Discussionmentioning
confidence: 82%
“…Other authors have examined venting the canal during intramedullary reaming but the significance in the oncologic population has yet to be elucidated [12][13][14]. Use of the RIA in animal models has demonstrated lower numbers of pulmonary emboli and lower intramedullary pressures when compared with traditional reaming [15,16]. In our small series, 6 patients had pulmonary metastases and compromised lung function, while 5 patients had brain metastases.…”
Section: Discussionmentioning
confidence: 82%
“…When 2 groups of intact sheep femurs were reamed, one with a Rinsing Suction Reamer (RSR) and the other with a conventional reamer, the RSR group showed no increase in intramedullary pressure over normal physiologic values, decreased fat intravasation into the pulmonary circulation, and improved cardiac and pulmonary hemodynamics [6]. In pigs reamed with the RIA there is evidence of improved cardiopulmonary function and fewer pulmonary emboli [7]. A subsequent study by the same group found decreased pulmonary activation of coagulation and fibrinolysis in the RIA group [8].…”
Section: Acute Care Of Femur Fracturesmentioning
confidence: 99%
“…21 Studies of nail placement in animals have demonstrated that the RIA device minimizes the increase in intramedullary pressure and fat intravasation associated with canal reaming. [9][10][11] Husebye et al 11 illustrated this in a sheep model by measuring intramedullary pressures at various times during the nailing of femur fractures with either the RIA device or traditional reamer. They found that pressures were signifi cantly lower during reaming with the RIA (mean, 33Ϯ8 mm Hg) than the traditional reamer (mean, 188Ϯ38 mm Hg), but there was no signifi cant difference at other points of the surgery, including nail insertion.…”
Section: C 4b 4amentioning
confidence: 99%
“…In nononcologic cases, use of the RIA device has been shown to decrease the rate of marrow intravasation and the number of pulmonary emboli compared with a standard femoral reamer. [9][10][11] The purpose of this study was to demonstrate that malignant cells could be retrieved by using a RIA during intramedullary fi xation of femoral lesions. By capturing a tumor that otherwise would have been forced into the systemic circulation, use of the RIA may decrease the risk of malignant embolization associated with this procedure.…”
mentioning
confidence: 99%